Digital Transformation: The Role Of Information Systems In Enhancing Efficiency - Muhammad Irwansyahputra; Fastabiqul Khairot (Journal on Economics, Management and Business Technology, 2025)
This research aims to understand and analyze how the digital transformation process can enhance relevant information systems, as well as how these digital information systems can improve operational efficiency in manufacturing companies in Indonesia. The research method uses a qualitative descriptive approach with purposive sampling for data collection, and the data is gathered through documentation study. Based on the research results, it can be concluded that information systems can become more relevant through the digital transformation process by analyzing organizational needs, modernizing technology infrastructure, digitizing business processes, integrating new technologies, building system integration, and implementing monitoring and analytics. Additionally, it can be concluded that digital information systems can improve business operational efficiency by automating operational processes, integrating data and systems, enabling faster and more accurate decision-making, reducing operational costs, and facilitating overall digital transformation.